Current Challenges, Opportunities and Global Perspectives of Criminal Law; Milestones of Law in Central Europe - Jozef Čentéš; Sara Zsemlyová; Roland Hochmann (Bratislava Law Review, 2025)
This report summarises the proceedings of the Criminal Law Section at the Milestones of Law in the Central European Area 2025 conference. A total of 43 contributions addressed current legislative reforms, practical challenges in criminal justice, the impact of technology, human rights protection, and ethical considerations. The academic discourse reflected the dynamic evolution of criminal law and the necessity of its continuous adaptation to emerging legal and societal challenges.